Design of conflict management procedures based on blockchain technology - Montecinos Ohlagaray, Rodolfo (2022)
Blockchain technology is expected to change the way in which the exchange of goods and services is developed, the management of conflicts, and will substantially influence the process of state modernisation. The current research aims to be a simple organisational and theoretical guide that provides a strategy for the process of conflict management in the state sphere. This is based on the imperative need to modernise the current public system, based on the division of powers. This article fundamentally emphasises three concordant ideas: first, that blockchain technology helps to automate certain tasks, thus facilitating access to a decentralised space independent of a central control authority. It democratises and makes management and decision-making processes transparent, allowing all those involved to be examined on an equal footing, and third, it aims to maintain the necessary manual intervention on the part of the State, in order to concentrate its work on complex tasks, thus ensuring the essential maintenance of its status quo, leaving purely administrative tasks in the hands of technology.